1999
DOI: 10.1046/j.1365-2141.1999.01483.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement‐induced procoagulant alteration of red blood cell membranes with microvesicle formation in paroxysmal nocturnal haemoglobinuria (PNH): implication for thrombogenesis in PNH

Abstract: Summary. Complement-induced procoagulant alteration of red blood cell (RBC) membranes in paroxysmal nocturnal haemoglobinuria (PNH) was examined. Microvesicles, de®-cient in acetylcholinesterase, were generated and released from PNH RBC upon complement activation. The microvesicles generated from complement-activated PNH RBC accelerated factor Xa-dependent plasma coagulation more than those generated from RBC by the treatment with ionophore A23187. When assessed by factor Xa-catalysed prothrombin activation, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
2
19
0
1
Order By: Relevance
“…MP release, generally accompanied by the loss of transversal phospholipid asymmetry leading to PS exposure, occurs during cell ageing and in disease states (Allan et al, 1982) or in in vitro conditions as the increase of intracellular Ca 2+ induced by an ionophore (Allan & Thomas, 1981). PS exposure and/or procoagulant MP generation in RBC can be induced by various mechanisms, such as intracellular calcium increase (Dekkers et al, 1998), PKC activation (de Jong et al, 2002) and ATP depletion (Beleznay et al, 1997); C5b-9 deposition on cell membranes is one such mechanism, in RBC as well as platelets (Wiedmer et al, 1993;Ninomiya et al, 1999). Our study demonstrated that the accumulation of C¢ MAC on RBC induces procoagulant MP release, which was shown both functionally by IIa generation assay and phenotypically by FCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MP release, generally accompanied by the loss of transversal phospholipid asymmetry leading to PS exposure, occurs during cell ageing and in disease states (Allan et al, 1982) or in in vitro conditions as the increase of intracellular Ca 2+ induced by an ionophore (Allan & Thomas, 1981). PS exposure and/or procoagulant MP generation in RBC can be induced by various mechanisms, such as intracellular calcium increase (Dekkers et al, 1998), PKC activation (de Jong et al, 2002) and ATP depletion (Beleznay et al, 1997); C5b-9 deposition on cell membranes is one such mechanism, in RBC as well as platelets (Wiedmer et al, 1993;Ninomiya et al, 1999). Our study demonstrated that the accumulation of C¢ MAC on RBC induces procoagulant MP release, which was shown both functionally by IIa generation assay and phenotypically by FCM.…”
Section: Discussionmentioning
confidence: 99%
“…The most important factor related to the poor prognosis of PNH is the complication of visceral thrombosis, cerebrovascular thromboembolism and pulmonary embolism (Ziakas et al, 2008). Several factors involved in thrombogenesis in PNH have been proposed: (i) chronic haemolysis, (ii) impaired fibrinolytic system, (iii) microparticles (MPs) released from injured platelets and vascular endothelia (Ploug et al, 1992;Wiedmer et al, 1993;Ninomiya et al, 1999;Simak et al, 2004). Complement (C¢) sensitivity of PNH red blood cells (RBC) is due to a deficiency in the expression of glycosyl-phosphatidylinositol (GPI)-anchored membrane proteins with C¢-regulatory activity, CD55 and CD59, on PNH-affected RBC (Wilcox et al, 1991;Parker et al, 2005;Brodsky, 2008).…”
mentioning
confidence: 99%
“…117,118 This is probably primarily a result of the potentiation of C1 inhibitor 122 but may also be caused by inhibition of both the classic and alternative pathway of C3 convertases as well as interference with the assembly of the C5b-9 complex. 123,124 Complement activation on PNH red blood cells induces procoagulant alteration of the red cell membranes, 98 but inhibition of complement-mediated lysis of PNH red cells by heparin and lowmolecular-weight heparin did not result in the inhibition of complement-induced procoagulant alteration of PNH red cells. 118 This suggests the principle mechanism of heparin action in this setting is through the interaction with C5b-9 and not through the potentiation of C1 inhibitor.…”
Section: Prevention Of Thrombosismentioning
confidence: 99%
“…The rate of NO depletion correlates with the severity of intravascular hemolysis of which LDH is a sensitive marker. 94 In addition to hemoglobin decompartmentalization and NO scavenging, intravascular hemolysis also releases erythrocyte arginase, an enzyme that converts L-arginine, the substrate for NO synthesis, to ornithine, thereby further reducing the systemic availability of NO 95 ( Figure 3 Circulating procoagulant microvesicles in association with red blood cells have also been described, 98 although other investigators have found this source to be very low.…”
mentioning
confidence: 99%
“…Identyfikacja pacjentów obciążonych wysokim ryzykiem nocnej napadowej hemoglobinurii Hemoliza wewnątrznaczyniowa w wielu mechanizmach prowadzi do stanu nadkrzepliwości. W wyniku rozpadu erytrocytów uwalniają się mikrocząstki błonowe bogate w PS [23]. Wolna Hb oraz niedobór NO powodują nasilenie adhezji i agregacji PLT.…”
Section: Powikłania Zakrzepowo-zatoroweunclassified